Production of phenolic hydrocarbons from organosolv lignin and lignocellulose feedstocks of hardwood, softwood, grass and agricultural waste - Son, Deokwon; Gu, Sangseo; Choi, Jae-Wook; Suh, Dong Jin; Jae, Jungho; Choi, Jungkyu; Ha, Jeong-Myeong (한국공업화학회, 2019)
Organosolv lignin extracted from the four representative lignocellulose feeds of oil palm empty fruit bunch (agricultural waste), oak (hardwood), pine (softwood) and Miscanthus giganteus (grass) is depolymerized using Ru/H-zeolite beta to produce phenolic hydrocarbons. The bulky methoxy functionality, which is rich in oak and pine, sterically hindered the ether bonds, decreasing the yields of phenolic monomers and improving the beta-beta coupling to repolymerize lignin fragments. Both depolymerization and repolymerization are improved at a higher reaction temperature. The structures and the reaction behavior of organosolv lignin are observed using NMR, GPC, N-2-physisorption, SEM and DLS analysis methods. (C) 2018 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.